Application of power-force-velocity profiling to "icss" disciplines - Fessl, I.; Fritz, J.; Kröll, J. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
The ability to accelerate the body and to produce high mechanical power during ballistic push-offs are considered physical performance determinants in various winter sport disciplines. The success of ballistic performances is determined by the peak power output as well as by the individual contribution of force and velocity (P-F-v profile). P-F-v profiles are characterized by the strong linear relationship between force and velocity of the propulsive phase obtained through jum ps with different loaded conditions. Each jump is represented as one data point in the P-F-v chart (Jaric, 2015). P-F-v profiling is increasingly applied in performance diagnostics because it provides more sophisticated information about the athlete's neuromuscular System and displays the individual makeup of their muscular mechanical capabilities (Jaric, 2015; Morin & Samozino, 2016). The outcome variables of P-F-v profiles, calculated by extrapolating the linear F-v-relationship until its interception with the x- and y-axis, are: Fo = theoretical maximal force, vo = theoretical maximal velocity, theoretical maximal power (Pmax; F° 4V° ), and the slope (Sfv) of the linear F-v-relationship (Giroux et al., 2014; Samozino et al., 2008). The outcome variables of the P-F-v profiles provide information for individualized training practices and can be used as a simple tool to monitor performance (Morin & Samozino, 2018). Individualized training programs based on the information of P-F-v profiles led to greater improvements in jum p height compared to "one-size-fits-all" training programs (Jimenez-Reyes et al., 2019). The approach using P-F-v profiling is already applied in several sports like football, rugby, and track and field (de Lacey et al., 2014; Delaney et al., 2018; Schleichardt et al., 2019). Each sport places specific demands on the neuromuscular system and thus leads to differing P-F-v profiles. The information obtained through P-F-v profiles can be used for team analysis and comparisons to identify sport-, gender- or age-specific P-F-v profiles. Therefore, the approach of P-F-v profiling is a feasible tool for performance diagnostics in training centers focused on winter sport disciplines. Alpine skiing (AS), ski jumping (Ski-J) and cross-country skiing (XC) require high muscle mechanical power of the lower limbs but the manner of power production and application is different in each discipline. In AS high muscular power is required at each turn while Ski-J athletes need to obtain the highest possible muscular power once at the take-off (Hydren et al., 2013; Schwameder, 2008). XC-athletes need high muscular power in sprint situations which got more important since the introduction of the sprint-event (Stöggl et al., 2011). Therefore, the main aim of the study was to compare the lower limb P-F-v profiles of young elite athletes from alpine skiing (AS), cross-country skiing (XC), and ski jumping (Ski-J). An additional aim was the application and adjustment (r2, remove outliers) of Samozino's Simple Method for the three different winter sport disciplines to assess the lower limb P-F-v profiles. It was hypothesized that differences would be found in the in the P-F-v outcome variables (Fo, vo, Pmax and Sfv) between AS, XC, and Ski-J athletes based on the differing sport-specific neuromuscular demands and that the adjustment of the r2 would lead to a higher quality of the individual P-F-v profile.